Redefining Dental Practice in the AI Era: Bridging Clinical Expertise with Intelligent Technologies - Dhopte, Ashwini; Mir, Faheem; Alzaqzouq, Rana Jamal; Khatri, Manjari; Saha, Ayan; Singh, Vikas (Bangladesh Journal of Medical Science, 2026)
Introduction of dental practice with the concept of artificial intelligence (AI) is an idea that is a radical change in the conceptualization of oral healthcare delivery and experience. This editorial review discusses the changing paradigm of AI in dentistry, which includes the use of AI in diagnostic imaging interpretation, treatment planning, clinical decision support, and prosthetic design. At the same time, though the AI technologies prove to be incredibly effective in pattern recognition, detecting diseases and performing predictive analytics, their implementation into the clinical process causes significant questions concerning the professional responsibility, educational readiness, ethical implementation, and maintenance of the humanistic principles of patient care. Combination of the old clinical knowledge with clever computing enables unheard of possibilities to improve the quality of diagnosis and treatment. Nevertheless, these benefits can only be actualized with a careful adoption that makes AI an addition and not a substitution of clinical judgment. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S7-S10